2020
DOI: 10.1177/0265532220927751
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of TOEFL® Primary™ repeaters: How much score change occurs?

Abstract: In this study, we examined how much change in TOEFL® Primary™ listening and reading scores can be expected in relation to the time interval between test administrations. The test records of 5213 young learners of English (aged 8–13 years) in Japan and Turkey who repeated the tests were analyzed to examine test scores as a function of time interval. The effect of time on test scores was analyzed with a multilevel modeling approach, allowing both initial scores and rate of change among individual test takers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Longitudinal data have also arisen from international testing contexts, enabling us to examine empirically the development of young EFL learners’ English skills in different educational contexts. For example, an analysis of over 5,000 EFL test records from repeat test takers in Turkey and Japan—assessing the children’s reading, speaking, and listening skills—showed that, contrary to the commonly held view that children’s language development is faster than that of adults, young EFL learners’ test scores do not increase rapidly over a short period, although there was a great deal of variability at the individual student level (Cho & Blood, 2020). The same data also suggested the effects of educational contexts on the amount of score change.…”
Section: From Infancy To Adolescence: a Burgeoning And Increasingly Diverse Fieldmentioning
confidence: 99%
“…Longitudinal data have also arisen from international testing contexts, enabling us to examine empirically the development of young EFL learners’ English skills in different educational contexts. For example, an analysis of over 5,000 EFL test records from repeat test takers in Turkey and Japan—assessing the children’s reading, speaking, and listening skills—showed that, contrary to the commonly held view that children’s language development is faster than that of adults, young EFL learners’ test scores do not increase rapidly over a short period, although there was a great deal of variability at the individual student level (Cho & Blood, 2020). The same data also suggested the effects of educational contexts on the amount of score change.…”
Section: From Infancy To Adolescence: a Burgeoning And Increasingly Diverse Fieldmentioning
confidence: 99%
“…Over the years, research has been conducted for these assessments in order to support the validity of test scores and their uses. For instance, in the context of the TOEFL Primary tests, studies have investigated content representativeness of the tests (Hsieh, 2016), YLs’ perceptions of critical components of the assessment (Cho & So, 2014; Getman, Cho, & Luce, 2016), YLs’ test-taking strategies (Gu & So, 2017), the relationship between test performance and test taker characteristics (Lee & Winke, 2018), the use of the test for different purposes such as a measure of progress (Cho & Blood, in press), and standard-setting studies mapping scores to the CEFR levels (Papageorgiou & Baron, 2017).…”
Section: Assessment Of Learningmentioning
confidence: 99%
“…Unfortunately, there were few studies carried out to explore these constraints. Most studies investigated students' difficulties in answering the TOEFL test items in general (Cho & Blood, 2020;Ginther & Yan, 2018;Halim & Ardiningtyas, 2018;Staples et al, 2018;Syakur, 2019), or only in the Listening and Reading sections (Nazri et al, 2020;Samad et al, 2017;Silviyanti et al, 2020;Zalha et al, 2020). These studies confirmed that limited time, fewer basic skills, less practice, less motivation, and students' differences were the main factors affecting the difficulties in facing the TOEFL test.…”
Section: Introductionmentioning
confidence: 96%